Development of Educational Leaflet for Genetic Counseling and Premarital Screening of Thalassemia for Prospective Couples - Setiawan, Henri; Rahman, Irpan Ali; Hidayat, Nur; Marliany, Heni; Rahayu, Yuyun (Genius Journal, 2024)
Introduction: Thalassemia is a common hereditary blood disorder with a significant impact on public health, particularly in high-prevalence areas. Genetic counseling and premarital screening are critical for educating couples at risk, helping to reduce the incidence of thalassemia. However, there is often a lack of accessible and comprehensible information on this topic for prospective couples, especially at the community health level. Objective: This study aimed to develop an educational leaflet tailored for prospective couples, focusing on genetic counseling and premarital screening for thalassemia. The leaflet is designed to enhance awareness, provide clear information, and encourage informed decision-making among couples. Method: A descriptive research design was employed to create and validate the educational leaflet. The development process included a needs assessment through surveys and focus group discussions with nurse educators and couples in the target population. Content was adapted based on expert feedback from genetic counselors and nurses educators to ensure accuracy, readability, and cultural relevance. Result: The finalized leaflet contains essential information on thalassemia, genetic counseling, and the importance of premarital screening. It is structured in a user-friendly format, including illustrations and a simplified language level to facilitate understanding. Conclusion: The educational leaflet effectively provides prospective couples with critical information on thalassemia, genetic counseling, and premarital screening. This tool can serve as a valuable resource in public health centers to promote awareness and preventive measures for hereditary diseases. Further research is recommended to evaluate its long-term impact on reducing thalassemia incidence.